Pengaruh Variasi Kecepatan Angin Terhadap Kinerja Generator - Fanji Azhary Arsal; Satrio Dwi Nugroho Nugroho; Shindy Aliffianti Ulfiah Ulfiah; Roy Bayu Negara Bayu; Muhammad Najmul Fadli Najmul; Yani Kamisa Putri Kamisa (Teknosia, 2025)
Wind power generation systems, wind speed has a significant impact on generator performance. Variations in wind speed can affect the reliability, efficiency, and output power of the system. The purpose of this study is to examine the relationship between changes in wind speed and generator performance, including energy conversion efficiency, output current, and output voltage. The study methodology includes actual measurements on a wind turbine-based generation system. The findings show that while higher wind speeds tend to increase generator output power, generator performance decreases drastically at low wind speeds, which can impact the reliability of electricity supply.